Disruption of purine de novo synthesis pathway impairs membrane homeostasis, intracellular survival, and virulence of Brucella melitensis - Yang, Guangyu; Li, Mengsi; Li, Yang; Chen, Simin; Qu, Jing; Li, Jihong; Wang, Shaohui; Bao, Yanqing; Qi, Jingjing; Dou, Yafeng; Tian, Mingxing (Frontiers in Microbiology, 2025)
IntroductionBrucellosis is a significant zoonotic infectious disease caused by Brucella. As a facultative intracellular pathogen, the ability of Brucella to acquire essential nutrients within host cells is critical for its intracellular survival and pathogenicity. Previous studies have indicated that disruption of the de novo purine biosynthesis pathway significantly attenuates the virulence of Brucella, although the underlying mechanisms remain incompletely understood.MethodsUsing Brucella melitensis M5 as the parental strain, we constructed a deletion mutant and a complemented strain of the key purine biosynthesis gene purD (encoding phosphoribosylamine–glycine ligase) via homologous recombination. Bacterial growth and stress sensitivity were assessed. Membrane permeability was evaluated using propidium iodide (PI) and 1-N-phenylnaphthylamine (NPN), while lipid biosynthesis was examined via Nile red staining. Additionally, intracellular survival was tested in cell infection models, and overall virulence was evaluated in a mouse model.ResultsDeletion of purD disrupted de novo purine synthesis and impaired bacterial growth. The mutant exhibited increased sensitivity to the anionic detergent sodium dodecyl sulfate, reduced membrane permeability, and altered lipid biosynthesis. Furthermore, the purD mutant showed significantly reduced ability to invade and survive within host cells, primarily due to insufficient purine acquisition. In mice, the mutant displayed reduced spleen and liver colonization, with diminished splenomegaly and granuloma formation.DiscussionThis study demonstrates that de novo purine biosynthesis is critical for Brucella membrane integrity, intracellular survival, and full virulence. These findings highlight this pathway as a promising target for developing attenuated vaccines and novel antimicrobials against brucellosis.